Comparison of Anthropometric Indices in Relation to Physical Activity Levels Among University Students - Valdez López, Alison Gabriela; Quiroga, Elizabeth; Ballesteros López, Leonardo Gabriel (Revista Ecos de la Academia, 2025)
Anthropometric indices are essential for determining risks associated with malnutrition, whether due to weight deficit or excess, and promote well-being strategies depending on physical activity. This study analyzed the relationship between anthropometric indices: body mass index (BMI), waist-to-hip ratio (WHR), and waist-to-height ratio (WHtR) and the level of physical activity in 646 students from the Technical University of Ambato, using the International Physical Activity Questionnaire (IPAQ). The results showed that BMI was the most affected by physical activity, presenting a significant correlation with moderate physical activity (P<0.05), indicating normal values in participants. Light physical activity was positively associated with BMI and WHtR (P < 0.05), indicating that students with low physical activity had higher values in these anthropometric indices. Vigorous activity was associated with WHR (P < 0.05) but did not show a clear effect on BMI and WHtR. In conclusion, anthropometric indices are sensitive to physical activity and vary depending on the intensity and type of exercise. Promoting adequate physical activity is essential to improving body composition and nutritional status.